On-farm technologies in social context: Improving local adaptive capacities and inclusive scaling mechanisms in North Shewa Zone, Ethiopia - Worku, Tigist; Habermann, Birgit (International Livestock Research Institute, 2022)
A presentation on how to improve local adaptive capacities and inclusive scaling mechanisms for climate-smart agriculture in Ethiopia. It was delivered at the inception workshop for the CGIAR Initiative for Livestock and Climate by Birgit Habermann